Seroprevalence and factors associated with Toxoplasma gondii-, Neospora caninum- and Coxiella burnetii-infections in dairy goat flocks from Costa Rica - Dolz, Gaby (2018)
A total of 391 goats from 13 dairy flocks from all Costa Rican regions were analyzed for Toxoplasma gondii-, Neospora caninum- and Coxiella burnetii-related seroprevalence by enzyme-linked immunosorbent assays (ELISA). Additionally, a risk factor analysis for these parasitic infections was performed based on a questionnaire considering several environmental and housing/management factors. A total of 62.1% (243/391) of individual serum samples revealed seropositive for T. gondii, 7.9% (31/391) for N. caninum, and 1.8% (7/391) for C. burnetii. At herd level, the overall seroprevalence for T. gondii was 100%, for N. caninum 69.2% and for C. burnetii 7.7%. However, no clinical signs related to toxoplasmosis, neosporosis or Q fever were apparent in these flocks. T. gondii-related risk factors were the contact with cats (OR=3.44; CI 95%; 2.0–5.91), dogs (OR=5.75; CI 95%; 2.84–11.66), and white-tailed deer (Odocoileus virginianus) (OR=0.15; CI 95%; 0.08–0.26) within or around the farms. The presence of reproductive males in each flock (OR=0.32; CI 95%; 0.14–0.74) and the coexistence of sheep (OR=0.46; CI 95%; 0.2–1.08) and cattle (OR=5.94; CI 95%; 1.70–20.78) revealed as protective and risk factors respectively for N. caninum infections. This study determined for the first time the seroprevalences of N. caninum, T. gondii and C. burnetii in Costa Rican goat flocks. Particularly, the high withinherd seroprevalences determined for T. gondii requires further surveillance to complement these findings.